HUBUNGAN POLA KOMUNIKASI DENGAN KEDISIPLINAN DAN MOTIVASI SANTRI PENGHAFAL AL QURAN DI PONDOK TAHFIDZ AL QURAN IBNU JAUZI BOGOR - Muhammad Ziyad; Ibdalsyah Ibdalsyah; Akhmad Alim (Universitas Pahlawan Tuanku Tambusai, 2022)
Communication is a basic human need. Because through communication, humans can disseminate information, get to know each other, exchange views to solve a problem. Communication is not only limited to socializing. Communication also takes part in the teaching process, motivating in the disciplined process of memorization. This study aims to determine the success rate of communication patterns, the level of discipline and motivation of students' memorization, as well as to determine the relationship of communication patterns with the discipline and motivation of students' memorization at the Tahfidz Al-Qur'an Islamic Boarding School Ibnu Jauzi Bogor. This study uses quantitative research techniques with the correlation research method (correlation). The results of this study indicate that the pattern of communication has no relationship with the discipline of memorizing students, by getting the results of the Sig. (2-tailed) 0.195, if the result is Sig. (2-tailed) > 0.05 = no correlation. The pattern of communication with motivation has no correlation, namely getting the value of Sig. (2-tailed) 0.360. Discipline and motivation to memorize students not only depend on communication patterns, but can be influenced by internal factors or other external factors. Keyword : Communication Pattern, Discipline and Motivational